Heterogenität von Hedgefondsindizes - Thomas Heidorn; Christian Hoppe; Dieter G. Kaiser (HfB - Business School of Finance & Management, 2006)
Most research on the performance and risk of hedge funds are based on calculations that just use the data from one index provider. Also most product providers and even more and more investors are using hedge fund indices for benchmarking purposes. As some academic articles pointed out, the world of hedge fund indices is very heterogeneous. So the empirical results on the optimal hedge fund allocation an investor would obtain by using the indices of one data provider could severely change if he would use another subset of indices. This paper analyses the heterogeneity of hedge fund indices that results from the fact that each index provider looks at a different subset of underlying hedge funds. Therefore we calculate different risk and return measures for the data series of six different hedge fund index providers and highlight the observed differences. In a next step, we rank the results we obtained, to find out which composite and strategy indices from which data provider are best used for benchmarking purposes from the point of view of the investor.
urn:nbn:de:101:1-2008082777
Keywords: G11; G15; G24; 330; Heterogenität; Volatilität; Sharpe Ratio; Sterling Ratio; Calmar Ratio; Omega; Autokorrelation; Sortino Ratio; Schiefe; Wölbung; Kurtosis; Persistenz